Homicide, gender and responsibility: an international perspective - Fitz-Gibbon, Kate; Walklate, Sandra (Routledge studies in crime and society, 2016)
Introduction: homicide, gender and responsibility / Kate Fitz-Gibbon and Sandra Walklate -- Making sense of the boundaries between homicide, gender and responsibility -- A question of provocation or responsibility? : revisiting the case of Ruth Ellis and David Blakely / Anette Ballinger -- Murder, manslaughter and domestic violence / Julie Stubbs -- Representing intimacy, gender and homicide : the validity and utility of common stereotypes in law / Myrna Dawson -- Constructions of masculinity and responsibility in the sentencing of children who commit lethal violence / Kate Fitz-Gibbon -- Murderousness in war : from mai lai to marine a / Sandra Walklate and Ross McGarry -- Blurring the boundaries between homicide, gender and responsibility -- "He seems to come out as a personally cruel person" : perpetrator re-presentations in direct murder cases at the ICTY / Anette Bringedal Houge -- Lethal violence and legal ambiguities : deaths in custody in Australia's offshore detention centres / Alison Gerard and Tracey A. Kerr -- Attributing criminal responsibility for workplace fatalities and deaths in custody : corporate manslaughter in Britain and Ireland / David Doyle and Joe McGrath -- Conclusion concluding thoughts on homicide, gender and responsibility / Kate Fitz-Gibbon and Sandra Walklate